2016
DOI: 10.1002/advs.201600400
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of Lithium Metal Anode via Hybrid Ionic Liquid Electrolyte toward Stable Li Plating/Stripping

Abstract: Hybrid electrolyte of ionic liquid and ethers is used to passivate the surface of Li metal surface via modification of the as‐formed solid electrolyte interphase with N‐propyl‐N‐methylpyrrolidinium bis(trifluoromethanesulfonyl)amide (Py13TFSI), thereby reducing the side reactions between the Li metal and electrolyte, leading to remarkably suppressed Li dendrite growth and mitigating Li metal corrosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
142
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(144 citation statements)
references
References 36 publications
2
142
0
Order By: Relevance
“…For decades, tremendous efforts have been made to improve the electrochemical performance and cycling life of the Li metal anodes. Studies have shown that the deposition behavior and interface stability of Li metal anodes can be greatly reinforced by modifying the electrolyte and additives, engineering protective interface layers, and constructing 3D host structures for Li metal . Among various approaches, the Li host structures have attracted considerable interest because they are effective in regulating Li deposition, suppressing the growth of Li dendrites, reducing the local current density, and homogenizing the Li‐ion flux.…”
mentioning
confidence: 99%
“…For decades, tremendous efforts have been made to improve the electrochemical performance and cycling life of the Li metal anodes. Studies have shown that the deposition behavior and interface stability of Li metal anodes can be greatly reinforced by modifying the electrolyte and additives, engineering protective interface layers, and constructing 3D host structures for Li metal . Among various approaches, the Li host structures have attracted considerable interest because they are effective in regulating Li deposition, suppressing the growth of Li dendrites, reducing the local current density, and homogenizing the Li‐ion flux.…”
mentioning
confidence: 99%
“…[9,10] It is worth noting that each of the strategies is atrade-off between advantages and shortcomings,a nd the issues of Li metal anode mentioned above have not yet been completely addressed. Therefore,i ti sr easonable that great efforts are devoted to creating as table and uniform protective layer at the electrode/electrolyte interface via in situ or ex situ methods.I n-situ formation of protection layers on Li metal surface is usually achieved by tailoring solvents, [11] Li salts, [12] and electrolyte additives. [9,13] These layers generally have higher strength and thickness than the native solid electrolyte interface (SEI) layers,a nd therefore the electrochemical performances can be enhanced.…”
mentioning
confidence: 99%
“…[6] The Li dendrite formation is due to the cracks formed in the insoluble solid-electrolyte interphase (SEI) layer between Li metal and electrolyte, as a result of drastic volume changes during continuous Li stripping/plating. [9,10] Various routes have thus been developed to restraint he growth of dendrites, including stabilizing the SEI layer by optimizingt he solvents, [11] lithiums alts, [4,12,13] and/ore lectrolyte additives; [14,15] introducing high-modulus solid electrolytes (such as lithium garnets [16][17][18] and composite electrolyte [19] )t op hysically impede dendrite infiltration;a nd building an interface layer on the lithium metal as an artificial protective SEI layer [20] (such as SiO 2 , [21] Al 2 O 3 , [22][23][24] LiF, [25,26] and polymer [27] ). [3] These decompositionr eactions lead to increasingi nternal resistance, low Coulombic efficiency (CE), and bad cycling performance of LIBs.…”
Section: Introductionmentioning
confidence: 99%